Transperitoneal laparoscopic pyeloplasty: a single center experience of 28 cases - Chaudhary, Ranjit; Dausage, Chirag Shanti (International Surgery Journal, 2018)
Background: To evaluate prospectively the results obtained in 28 patients undergoing laparoscopic pyeloplasty through transperitoneal access. Methods: From January 2014 to June 2016, twenty-eight patients between 12 and 55 years old underwent laparoscopic pyeloplasty for primary ureteropelvic junction (UPJ) obstruction via a transperitoneal approach. Eighteen cases had the obstruction on the left side and the other ten on the right side. All patients had radiographic evidence of obstruction with signs, symptoms or deterioration of renal function. Anderson-Hynes dismembered pyeloplasty was performed in 25 patients and Fenger technique in the other 3 cases. Three patients had non-obstructing renal stones and underwent concomitant pyelolithotomy. Patients were evaluated clinically and by imaging in the postoperative period at 3 and 6 months and then followed-up annually. Results: The operative time ranged from 190 to 330 min. The average blood loss was 70 mL. Analgesic requirements were also minimal with patients requiring PCA for an average of 1.1 days. Average days to free fluids were 1.5 days. The mean hospital stay was 3.76 days. The time to return to normal activities ranged from 7 to 12 days. Crossing vessels were identified in 16 patients, intrinsic stenosis in 14 patients and 5 patients had high implantation of the ureter. There were no conversions to open. One patient had longer urinary fistula (9 days), 2 patients had prolonged ileus and 3 patients had port site infection. The follow up ranged from 6 to 72 months. From the later postoperative complications, 2 patients had re-stenosis. The success rate was 92.85%. Conclusions: Laparoscopic pyeloplasty has functional results comparable to conventional open technique. It offers less morbidity, with aesthetic and post-operative convalescence benefits and lower complication rates.